Thermodynamics of Pd–Mn phases and extension to the Fe–Mn–Pd system. (December 2015) - Povoden-Karadeniz, E.; Lang, P.; Moszner, F.; Pogatscher, S.; Ruban, A.V.; Uggowitzer, P.J.; Kozeschnik, E.
Abstract: A thermodynamic description of the Pd–Mn system and the extension to the Fe–Pd–Mn system is developed within the framework of the CALPHAD approach. Thermodynamic data of the Pd–Mn system are critically reviewed and parameters of thermodynamic phase descriptions are optimized by selective combination of experimental data from the literature as well as published and new first-principles results. Phase diagram data are obtained from published microscopic and x-ray analysis. A previous calorimetric study and density functional theory results deliver enthalpies of formation of intermetallic Pd–Mn phases, and assessed Mn-activities are compared with experimental data derived from electromotive force and isopiestic experiments. A large difference between calorimetric high-temperature CALPHAD-assessed and first-principles enthalpies at 0 K of the PdMn-B2 phase is revealed and discussed. For the extension to the Fe–Mn–Pd system, thermodynamic descriptions of Pd–Fe intermetallics are revised using recent experimental and theoretic thermodynamic standard data and measured temperatures of magnetic transformations from the literature. A comprehensive thermodynamic standard data set of the intermetallic phases PdMn-B2, PdMn-L10, Pd5 Mn3, Pd2 Mn, Pd3 Mn-D023, Pd3 Mn-L12, Pd3 Fe-L12, and PdFe-L10 is proposed. A set of experimental data of Fe-solubility in PdMn-L10, the phase compositions of the L10 -phase in equilibrium with austenite, and the observed austenite+liquid equilibrium is used for extensions of model descriptions to ternary Fe–Mn–Pd. Heat-treated Fe-rich Fe–Mn–Pd alloys containing 5–20 wt% Mn and 1–10 wt% Pd reveal considerable stabilization of the tetragonal PdMn-L10 by dissolved Fe leading to an increase of the solvus temperature by more than 650 K relative to pure PdMn-L10 . Assessed isothermal sections of the ternary Fe–Mn–Pd system are presented. Highlights: Thermodynamic properties of ordered intermetallic Mn–Pd phases are modeled. Model descriptions of phase extensions to the ternary Fe–Pd–Mn system are presented. The stability of PdMn phase is studied in heat-treated bio-degradable Fe-base alloy. T 0 of diffusionless fcc→bcc transformation in magnetic Fe–Pd–Mn alloy is evaluated.